Competitividad sostenible de la pequeña empresa: un modelo de promoción de capacidades endógenas para promover ventajas competitivas sostenibles y alta productividad - Vargas, Braulio (2008)
In the past three decades, the competitiveness and productivity of the small enterprise have been favored by the government, business action and technical cooperation, which have made signifi cant contributions regarding promotion, development and provision of technical assistance. In the developing economies of the Asia Pacifi c region, these efforts are explained by the fact that the small enterprise contributes without question, to job generation, local economic dynamics, collective effi ciency of business network, and economic growth. In the economies of the region, most contributions have been channeled through public policies with a focus on capacity building. Nevertheless, according to preliminary studies in the main business clusters in Peru, the government’s promotion actions have not had a steady effect in competitiveness and productivity. Evidence suggests that business development services have a limited effect as they depend solely on external interventions. In contrast, successful entrepreneurship relies more on endogenous capacities. This article introduces a framework of promotion of the productivity and sustained competitiveness in the small enterprise, laying stress on endogenous capacities and an effi cient arrangement of external interventions.